Juvenile literature and British society, 1850-1950 : the age of adolescence - Ferrall, Charles (Children's literature and culture ;, 2010)
In this study, Ferrall and Jackson argue that the Victorians created a concept of adolescence that lasted into the twentieth century and yet is strikingly at odds with post-Second World War notions of adolescence as a period of "storm and stress."